PENGARUH SOCIAL MEDIA MARKETING, E-WOM, DAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP CUSTOMER ENGAGEMENT - Ilham Tri Kusuma (2023)
Shopping has now become a basic activity to meet the daily needs of every individual. This encourages innovation from entrepreneurs in creating a platform for online shopping activities that is easily accessible to various groups. The purpose of this study is to test whether there is an effect of social media marketing, electronic word of mouth, and customer relationship management on customer engagement. The research design used in this research is a quantitative approach with a sample taken of 100 Lazada user respondents who live in Bekasi. The sampling technique was carried out by non-probability sampling with purposive sampling method. Data collection using a questionnaire and analysis using SmartPLS 4.0 application. The results of this research show that: (1) social media marketing has a positive and significant effect on customer engagement, (2) electronic word of mouth has a positive and significant effect on customer engagement and (3) customer relationship management has a positive and significant effect on customer engagement.